Barriers of Adopting Harvesting Technology Inmalaysian Oil Palm Industry - Mohd Nawi, Nur Syazwani; Md Deros, Baba; Nordin, Norani (INSInet Publications, 2014)
Nowadays, technology has been recognized as one of the strategic tools in enhancing the economic competitiveness of a country. In oil palm industry, many types of machinery were invented to assist workers to perform their work process. However, manual methods still remain as the most effective way of harvesting fresh fruit bunches (FFB) in oil palm industry. This situation may give negative impact to the Malaysian economy especially in terms of upstream productivity and sustainability. Therefore, the objective of this paper is to identify the factors that cause fresh fruit bunches harvesters to refuse or resist in using the new harvesting technology. Based on the literature of past studies, it was found that reasons the major identified are the large size and heavy weight, vibration, high cost, limited height of reach and difficult to access from palm to palm. In conclusion, these problems can be solved by incorporating ergonomic approach in the design of machinery for human use